Global Regulator PhoP is Necessary for Motility, Biofilm Formation, Exoenzyme Production, and Virulence of Xanthomonas citri Subsp. citri on Citrus Plants - Wei, Chudan (Genes (Basel), 2019)
Citrus canker caused by Xanthomonas citri subsp. citri is one of the most important bacterial diseases of citrus, impacting both plant growth and fruit quality. Identifying and elucidating the roles of genes associated with pathogenesis has aided our understanding of the molecular basis of citrus-bacteria interactions. However, the complex virulence mechanisms of X. citri subsp. citri are still not well understood. In this study, we characterized the role of PhoP in X. citri subsp. citri using a phoP deletion mutant, ΔphoP. Compared with wild-type strain XHG3, ΔphoP showed reduced motility, biofilm formation, as well as decreased production of cellulase, amylase, and polygalacturonase. In addition, the virulence of ΔphoP on citrus leaves was significantly decreased. To further understand the virulence mechanisms of X. citri subsp. citri, high-throughput RNA sequencing technology (RNA-Seq) was used to compare the transcriptomes of the wild-type and mutant strains. Analysis revealed 1017 differentially-expressed genes (DEGs), of which 614 were up-regulated and 403 were down-regulated in ΔphoP. Gene ontology functional enrichment and Kyoto Encyclopedia of Genes and Genomes pathway analyses suggested that the DEGs were enriched in flagellar assembly, two-component systems, histidine metabolism, bacterial chemotaxis, ABC transporters, and bacterial secretion systems. Our results showed that PhoP activates the expression of a large set of virulence genes, including 22 type III secretion system genes and 15 type III secretion system effector genes, as well as several genes involved in chemotaxis, and flagellar and histidine biosynthesis. Two-step reverse-transcription polymerase chain reaction analysis targeting 17 genes was used to validate the RNA-seq data, and confirmed that the expression of all 17 genes, except for that of virB1, decreased significantly. Our results suggest that PhoP interacts with a global signaling network to co-ordinate the expression of multiple virulence factors involved in modification and adaption to the host environment during infection.